2019
DOI: 10.1016/j.ecss.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of transcriptomic and biochemical parameters of Donax trunculus related to its infection by Bacciger bacciger (trematode parasite)

Abstract: Seasonal variation of transcriptomic and biochemical parameters of Donax trunculus related to its infection by Bacciger bacciger (trematode parasite)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previously, non‐destructive assessment has been achieved through monitoring of cercarial release in the laboratory (Taskinen, 1998a; Choo & Taskinen, 2015; Magalhães et al, 2017). However, recent work (Magalhães et al, 2017; Magalhães et al, 2019) has shown that this results in estimates of infection rates between 5 and 10 times less than reality, as determined by destructively dissecting the gonad. There is the possibility for cercarial monitoring to reach high accuracy: at elevated temperatures, Choo & Taskinen (2015) showed that this technique could reliably diagnose infection.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, non‐destructive assessment has been achieved through monitoring of cercarial release in the laboratory (Taskinen, 1998a; Choo & Taskinen, 2015; Magalhães et al, 2017). However, recent work (Magalhães et al, 2017; Magalhães et al, 2019) has shown that this results in estimates of infection rates between 5 and 10 times less than reality, as determined by destructively dissecting the gonad. There is the possibility for cercarial monitoring to reach high accuracy: at elevated temperatures, Choo & Taskinen (2015) showed that this technique could reliably diagnose infection.…”
Section: Discussionmentioning
confidence: 95%
“…The digeneans in a sporocyst stage generally utilize mollusks as the first intermediate host and invade a variety of vertebrates and invertebrates in the form of metacercaria (Littlewood, 2006). The metacercaria infection often results in retarded growth (Wegeberg and Jensen, 2003;Thieltges, 2006a); increased energy demand (Magalhães et al, 2019); manipulation of host behavior, leading the host to become conspicuous to their predators (Lafferty and Morris, 1996;Thomas and Poulin, 1998;Eliuk et al, 2020); and mortalities (Gordon and Rau, 1982;Jacobson et al, 2008;Magalhães et al, 2015). However, most metacercaria infections pose a relatively minor impact on hosts, as they do not reproduce in the host (Bower et al, 1994;Rhode, 2005).…”
Section: Introductionmentioning
confidence: 99%